STANDARDISATION OF SPECIFICATIONS FOR DIFFERENT TROLLING LURES - PILLAl, N SUBRAMONIA; MANOHARADOSS, R S; SULOCHANAN, P (Fishery Technology, 2025)
Fishing experiments were conducted with buffalo horn, woodenand galvanised iron jigs of different lengths and weights rigged introll lines. It was observed that jigs with 12 em length and 60 gweight were superior to others in luring seer fish. Fish head jigsof 60 g weight showed a higher efficiency index than those of50 and 70 g tried in these studies